Genome-wide association study on Northern Chinese identifies KLF2, DOT1L and STAB2 associated with systemic lupus erythematosus. (26th January 2021) - Song, Qin; Lei, Yao; Shao, Li; Li, Weiyang; Kong, Qingsheng; Lin, Zhiming; Qin, Xiao; Wei, Wei; Hou, Fei; Li, Jian; Guo, Xianghua; Mao, Yujing; et al.
Abstract: Objectives: To identify novel genetic loci associated with systemic lupus erythematosus (SLE) and to evaluate potential genetic differences between ethnic Chinese and European populations in SLE susceptibility. Methods: A new genome-wide association study (GWAS) was conducted from Jining, North China, on 1506 individuals (512 SLE cases and 994 matched healthy controls). The association results were meta-analysed with existing data on Chinese populations from Hong Kong, Guangzhou and Central China, as well as GWAS results from four cohorts of European ancestry. A total of 26 774 individuals (9310 SLE cases and 17 464 controls) were included in this study. Results: Meta-analysis on four Chinese cohorts identifies KLF2 as a novel locus associated with SLE [rs2362475; odds ratio (OR) = 0.85, P =2.00E-09]. KLF2 is likely an Asian-specific locus as no evidence of association was detected in the four European cohorts (OR = 0.98, P  =0.58), with evidence of heterogeneity ( P =0.0019) between the two ancestral groups. Meta-analyses of results from both Chinese and Europeans identify STAB2 (rs10082873; OR= 0.89, P =4.08E-08) and DOT1L (rs4807205; OR= 1.12, P =8.17E-09) as trans-ancestral association loci, surpassing the genome-wide significance. Conclusions: We identified three loci associated with SLE, with KLF2 a likely Chinese-specific locus, highlighting the importance of studying diverse populations in SLE genetics. We hypothesize that DOT1L and KLF2 are plausible SLE treatment targets, with inhibitors of DOT1L and inducers of KLF2 already available clinically.